The Training Evaluation in the Educational Governorates of Oman - Aladawi, Nassra Mohammed Salim (Journal of Educational and Psychological Sciences, 2022)
The training evaluation processes and techniques were not activated. The most used instrument was the questionnaire. There is no organizational structure to the process of the evaluation, it hasn’t an evidence or procedural specialist assessment team and does not take place within the scientific basis for evaluation of the planning and analysis. There aren’t any reports for the evaluation training implemented by the Center. The education training centers used the Excel to analyze the collected data, and Excel shows percentages only. The recommendations for that are: The process of evaluation at the training centers need to re-consideration of, and need more attention. The training centers need to build a manual for the process of training evaluation. They need to begin the preparation of an information base using the information of each evaluation to benefit in the subsequent evaluation.